Solve 26th question.
Attachments:
![](https://hi-static.z-dn.net/files/d2f/4892ea7f4d416f8edbf5cd18efc5df0e.jpg)
Answers
Answered by
17
Here is your answer :
Given,
Quadratic equation = ( 2k + 1 )x² - ( 7k + 2 )x + ( 7k - 3 ) = 0
Here,
Coefficient of x² ( a ) = ( 2k + 1 )
Coefficient of x ( b ) = - ( 7k + 2 )
Constant term ( c ) = ( 7k - 3 )
For any quadratic equation to have equal roots, its Discriminat ( D = b² - 4ac ) should be equal to zero.
=> D = 0
=> b² - 4ac = 0
Substitute the value of a, b and c.
=> [ -( 7k + 2 ) ]² - 4( 2k + 1 )( 7k - 3) = 0
=> ( -7k )² + ( -2 )² + 2( -7k ) ( -2 ) - ( 8k + 4 ) ( 7k - 3 ) = 0
=> 49k² + 4 + 28k -8k( 7k - 3 ) - 4( 7k - 3 ) = 0
=> 49k² + 4 + 28k - 56k² + 24k - 28k + 12 = 0
=> 49k² - 56k² + 28k + 24k - 28k + 4 + 12 = 0
=> -7k² + 24k + 16 = 0
=> - ( 7k² - 24k - 16 ) = 0
=> ( 7k² - 24k - 16 ) = 0
=> 7k² - 28k + 4k - 16 = 0
=> 7k( k - 4 ) + 4( k - 4 ) = 0
=> ( k - 4 ) ( 7k + 4 ) = 0
=>(k-4)= 0/(7k + 4 ) , ( 7k + 4 ) = 0/( k - 4 )
=> ( k - 4 ) = 0 , ( 7k + 4 ) = 0
=> k = 4 , 7k = -4
•°• k = 4 , ( -4/7 )
Now,
Quadratic equation = ( 2k + 1)x² - ( 7k + 2 )x + ( 7k - 3 ) = 0
Substitute k = 4,
=> ( 2 × 4 + 1 )x² - ( 7 × 4 + 2 )x + ( 7 × 4 - 3 ) = 0
=> ( 8 + 1 )x² - ( 28 + 2 )x + ( 28 - 3 ) = 0
=> 9x² - 30x + 25 = 0
=> ( 3x )² - 2 × ( 3x ) ( 5 ) + ( 5 )² = 0
Using identity :
[ a² - 2ab + b² = ( a - b )² ]
=> ( 3x - 5 )² = 0
=> ( 3x - 5 ) = √0
=> ( 3x - 5 ) = 0
=> 3x = 5
•°• x = ( 5/3 )
Zeroes = ( 5/3 ) and ( 5/3 ).
When, k = ( -4/7 )
=> ( 2k + 1 )x² - ( 7k + 2 )x + ( 7k - 3 ) = 0
Substitute k = ( -4/7 ),
=> [ 2( -4/7 ) + 1 ]x² - [ 7( -4/7 ) + 2 ]x + [ 7( -4/7 ) - 3 ] = 0
=> [ ( -8/7 ) + 1 ]x² - [ -4 + 2 ]x + ( -4 - 3 ) = 0
=> ( -1/7 )x² - ( -2 )x + ( -7 ) = 0
=> ( -1/7 )x² + 2x - 7 = 0
=> - [ ( 1/7 )x² -2x + 7 ] = 0
=> ( 1/7 )x² - 2x + 7 = 0
=> [ ( 1/√7 )x ]² - 2 [ (1/√7 )x ] ( √7 ) + ( √7 )² = 0
Using identity :
=> [ a² - 2ab + b² = ( a - b )² ]
=> [ ( 1/√7 )x - √7 ]² = 0
=> [ ( 1/√7 )x - √7 ] = 0
=> ( 1/√7 )x = √7
=> x = √7 × √7
•°• x = 7
Zeroes = 7 , 7
If k = 4 then zeroes are (5/3 ) and ( 5/3 ).
If , k = ( -4/7 ) then zeroes are ( 7 ) and ( 7 ).
Hope it helps !!
Given,
Quadratic equation = ( 2k + 1 )x² - ( 7k + 2 )x + ( 7k - 3 ) = 0
Here,
Coefficient of x² ( a ) = ( 2k + 1 )
Coefficient of x ( b ) = - ( 7k + 2 )
Constant term ( c ) = ( 7k - 3 )
For any quadratic equation to have equal roots, its Discriminat ( D = b² - 4ac ) should be equal to zero.
=> D = 0
=> b² - 4ac = 0
Substitute the value of a, b and c.
=> [ -( 7k + 2 ) ]² - 4( 2k + 1 )( 7k - 3) = 0
=> ( -7k )² + ( -2 )² + 2( -7k ) ( -2 ) - ( 8k + 4 ) ( 7k - 3 ) = 0
=> 49k² + 4 + 28k -8k( 7k - 3 ) - 4( 7k - 3 ) = 0
=> 49k² + 4 + 28k - 56k² + 24k - 28k + 12 = 0
=> 49k² - 56k² + 28k + 24k - 28k + 4 + 12 = 0
=> -7k² + 24k + 16 = 0
=> - ( 7k² - 24k - 16 ) = 0
=> ( 7k² - 24k - 16 ) = 0
=> 7k² - 28k + 4k - 16 = 0
=> 7k( k - 4 ) + 4( k - 4 ) = 0
=> ( k - 4 ) ( 7k + 4 ) = 0
=>(k-4)= 0/(7k + 4 ) , ( 7k + 4 ) = 0/( k - 4 )
=> ( k - 4 ) = 0 , ( 7k + 4 ) = 0
=> k = 4 , 7k = -4
•°• k = 4 , ( -4/7 )
Now,
Quadratic equation = ( 2k + 1)x² - ( 7k + 2 )x + ( 7k - 3 ) = 0
Substitute k = 4,
=> ( 2 × 4 + 1 )x² - ( 7 × 4 + 2 )x + ( 7 × 4 - 3 ) = 0
=> ( 8 + 1 )x² - ( 28 + 2 )x + ( 28 - 3 ) = 0
=> 9x² - 30x + 25 = 0
=> ( 3x )² - 2 × ( 3x ) ( 5 ) + ( 5 )² = 0
Using identity :
[ a² - 2ab + b² = ( a - b )² ]
=> ( 3x - 5 )² = 0
=> ( 3x - 5 ) = √0
=> ( 3x - 5 ) = 0
=> 3x = 5
•°• x = ( 5/3 )
Zeroes = ( 5/3 ) and ( 5/3 ).
When, k = ( -4/7 )
=> ( 2k + 1 )x² - ( 7k + 2 )x + ( 7k - 3 ) = 0
Substitute k = ( -4/7 ),
=> [ 2( -4/7 ) + 1 ]x² - [ 7( -4/7 ) + 2 ]x + [ 7( -4/7 ) - 3 ] = 0
=> [ ( -8/7 ) + 1 ]x² - [ -4 + 2 ]x + ( -4 - 3 ) = 0
=> ( -1/7 )x² - ( -2 )x + ( -7 ) = 0
=> ( -1/7 )x² + 2x - 7 = 0
=> - [ ( 1/7 )x² -2x + 7 ] = 0
=> ( 1/7 )x² - 2x + 7 = 0
=> [ ( 1/√7 )x ]² - 2 [ (1/√7 )x ] ( √7 ) + ( √7 )² = 0
Using identity :
=> [ a² - 2ab + b² = ( a - b )² ]
=> [ ( 1/√7 )x - √7 ]² = 0
=> [ ( 1/√7 )x - √7 ] = 0
=> ( 1/√7 )x = √7
=> x = √7 × √7
•°• x = 7
Zeroes = 7 , 7
If k = 4 then zeroes are (5/3 ) and ( 5/3 ).
If , k = ( -4/7 ) then zeroes are ( 7 ) and ( 7 ).
Hope it helps !!
Anonymous:
Let me edit it
Answered by
11
========================
HERE IS YOUR ANSWER ☞
========================
![given \: quadratic \: equation \: = > \\ \\ = > (2k + 1) {x}^{2} - (7k + 2)x + (7k - 3) = 0 \\ \\ here \\ = > a \: = (2k + 1) \\ = > b = (7k + 2) \\ = > c = (7k - 3) \\ \\ now \\ \\ = > d = {b}^{2} - 4ac \\ \\ = > d = {(7k + 2)}^{2} - 4 \times (2k + 1)(7k - 3) \\ \\ = > d = 49 {k}^{2} + 4 + 28 - 4(14 {k}^{2} + 7k - 6k - 3) \\ \\ = > d = - 7 {k}^{2} + 24k + 16 \\ \\ we \: know \: that \: for \: equal \: roots \: \\ \\ = > d = 0 \\ \\ = > - 7 {k}^{2} + 24k + 16 = 0 \\ \\ = > 7 {k}^{2} - 28k \: + 4k - 16 = 0 \\ \\ = > 7k(k - 4) + 4(k - 4) = 0 \\ \\ = > (7k + 4)(k - 4) = 0 \\ \\ then \\ \\ = > k = - \frac{4}{7} \: \: \: or \: \: \: \: k = 4 \\ \\ now \\ \\ plug \: the \: value \: of \: of \: = > \: k = 4 \: in \: equation \: we \: get \\ \\ = > (2k + 1) {x}^{2} - (7k + 2)x + (7k - 3) = 0 \\ \\ = > 9 {x}^{2} - 30x + 25 = 0 \\ \\ = > {(3x - 5)}^{2} = 0 \: \: \: \: \: \: ( {a}^{2} - 2ab + {b = {(a - b)}^{2} }) \\ \\ = > 3x - 5 = 0 \\ \\ = > x = \frac{5}{3} \\ \\ = > zeros = \frac{5}{3} \: and \: \frac{5}{3} \\ \\ now \\ \\ plug \: value \: = > k = - \frac{4}{7} \\ \\ = > (2( - \frac{4}{7} + 1) {x}^{2} - (7( - \frac{4}{7} ) + 2)x + (7( - \frac{4}{3} ) - 3) = 0 \\ \\ = > ( - \frac{1}{7} ) {x}^{2} + 2x - 7 = 0 \\ \\ = > \frac{1}{7} {x}^{2} - 2x + 7 = 0 \\ \\ = > {( \frac{1}{ \sqrt{7} }) }^{2} - 2( \frac{1}{ \sqrt{7} } x) \sqrt{7} + { \sqrt{7} }^{2} = 0 \\ \\ = > {( \frac{1}{ \sqrt{7} }x - \sqrt{7} )}^{2} = 0 \\ \\ = > \frac{1}{ \sqrt{7} } x = \sqrt{7 } \\ \\ = > x = 7 \\ \\ = > zeros \: = 7 \: and \: 7 given \: quadratic \: equation \: = > \\ \\ = > (2k + 1) {x}^{2} - (7k + 2)x + (7k - 3) = 0 \\ \\ here \\ = > a \: = (2k + 1) \\ = > b = (7k + 2) \\ = > c = (7k - 3) \\ \\ now \\ \\ = > d = {b}^{2} - 4ac \\ \\ = > d = {(7k + 2)}^{2} - 4 \times (2k + 1)(7k - 3) \\ \\ = > d = 49 {k}^{2} + 4 + 28 - 4(14 {k}^{2} + 7k - 6k - 3) \\ \\ = > d = - 7 {k}^{2} + 24k + 16 \\ \\ we \: know \: that \: for \: equal \: roots \: \\ \\ = > d = 0 \\ \\ = > - 7 {k}^{2} + 24k + 16 = 0 \\ \\ = > 7 {k}^{2} - 28k \: + 4k - 16 = 0 \\ \\ = > 7k(k - 4) + 4(k - 4) = 0 \\ \\ = > (7k + 4)(k - 4) = 0 \\ \\ then \\ \\ = > k = - \frac{4}{7} \: \: \: or \: \: \: \: k = 4 \\ \\ now \\ \\ plug \: the \: value \: of \: of \: = > \: k = 4 \: in \: equation \: we \: get \\ \\ = > (2k + 1) {x}^{2} - (7k + 2)x + (7k - 3) = 0 \\ \\ = > 9 {x}^{2} - 30x + 25 = 0 \\ \\ = > {(3x - 5)}^{2} = 0 \: \: \: \: \: \: ( {a}^{2} - 2ab + {b = {(a - b)}^{2} }) \\ \\ = > 3x - 5 = 0 \\ \\ = > x = \frac{5}{3} \\ \\ = > zeros = \frac{5}{3} \: and \: \frac{5}{3} \\ \\ now \\ \\ plug \: value \: = > k = - \frac{4}{7} \\ \\ = > (2( - \frac{4}{7} + 1) {x}^{2} - (7( - \frac{4}{7} ) + 2)x + (7( - \frac{4}{3} ) - 3) = 0 \\ \\ = > ( - \frac{1}{7} ) {x}^{2} + 2x - 7 = 0 \\ \\ = > \frac{1}{7} {x}^{2} - 2x + 7 = 0 \\ \\ = > {( \frac{1}{ \sqrt{7} }) }^{2} - 2( \frac{1}{ \sqrt{7} } x) \sqrt{7} + { \sqrt{7} }^{2} = 0 \\ \\ = > {( \frac{1}{ \sqrt{7} }x - \sqrt{7} )}^{2} = 0 \\ \\ = > \frac{1}{ \sqrt{7} } x = \sqrt{7 } \\ \\ = > x = 7 \\ \\ = > zeros \: = 7 \: and \: 7](https://tex.z-dn.net/?f=given+%5C%3A+quadratic+%5C%3A+equation+%5C%3A+%3D+%26gt%3B+%5C%5C+%5C%5C+%3D+%26gt%3B+%282k+%2B+1%29+%7Bx%7D%5E%7B2%7D+-+%287k+%2B+2%29x+%2B+%287k+-+3%29+%3D+0+%5C%5C+%5C%5C+here+%5C%5C+%3D+%26gt%3B+a+%5C%3A+%3D+%282k+%2B+1%29+%5C%5C+%3D+%26gt%3B+b+%3D+%287k+%2B+2%29+%5C%5C+%3D+%26gt%3B+c+%3D+%287k+-+3%29+%5C%5C+%5C%5C+now+%5C%5C+%5C%5C+%3D+%26gt%3B+d+%3D+%7Bb%7D%5E%7B2%7D+-+4ac+%5C%5C+%5C%5C+%3D+%26gt%3B+d+%3D+%7B%287k+%2B+2%29%7D%5E%7B2%7D+-+4+%5Ctimes+%282k+%2B+1%29%287k+-+3%29+%5C%5C+%5C%5C+%3D+%26gt%3B+d+%3D+49+%7Bk%7D%5E%7B2%7D+%2B+4+%2B+28+-+4%2814+%7Bk%7D%5E%7B2%7D+%2B+7k+-+6k+-+3%29+%5C%5C+%5C%5C+%3D+%26gt%3B+d+%3D+-+7+%7Bk%7D%5E%7B2%7D+%2B+24k+%2B+16+%5C%5C+%5C%5C+we+%5C%3A+know+%5C%3A+that+%5C%3A+for+%5C%3A+equal+%5C%3A+roots+%5C%3A+%5C%5C+%5C%5C+%3D+%26gt%3B+d+%3D+0+%5C%5C+%5C%5C+%3D+%26gt%3B+-+7+%7Bk%7D%5E%7B2%7D+%2B+24k+%2B+16+%3D+0+%5C%5C+%5C%5C+%3D+%26gt%3B+7+%7Bk%7D%5E%7B2%7D+-+28k+%5C%3A+%2B+4k+-+16+%3D+0+%5C%5C+%5C%5C+%3D+%26gt%3B+7k%28k+-+4%29+%2B+4%28k+-+4%29+%3D+0+%5C%5C+%5C%5C+%3D+%26gt%3B+%287k+%2B+4%29%28k+-+4%29+%3D+0+%5C%5C+%5C%5C+then+%5C%5C+%5C%5C+%3D+%26gt%3B+k+%3D+-+%5Cfrac%7B4%7D%7B7%7D+%5C%3A+%5C%3A+%5C%3A+or+%5C%3A+%5C%3A+%5C%3A+%5C%3A+k+%3D+4+%5C%5C+%5C%5C+now+%5C%5C+%5C%5C+plug+%5C%3A+the+%5C%3A+value+%5C%3A+of+%5C%3A+of+%5C%3A+%3D+%26gt%3B+%5C%3A+k+%3D+4+%5C%3A+in+%5C%3A+equation+%5C%3A+we+%5C%3A+get+%5C%5C+%5C%5C+%3D+%26gt%3B+%282k+%2B+1%29+%7Bx%7D%5E%7B2%7D+-+%287k+%2B+2%29x+%2B+%287k+-+3%29+%3D+0+%5C%5C+%5C%5C+%3D+%26gt%3B+9+%7Bx%7D%5E%7B2%7D+-+30x+%2B+25+%3D+0+%5C%5C+%5C%5C+%3D+%26gt%3B+%7B%283x+-+5%29%7D%5E%7B2%7D+%3D+0+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%28+%7Ba%7D%5E%7B2%7D+-+2ab+%2B+%7Bb+%3D+%7B%28a+-+b%29%7D%5E%7B2%7D+%7D%29+%5C%5C+%5C%5C+%3D+%26gt%3B+3x+-+5+%3D+0+%5C%5C+%5C%5C+%3D+%26gt%3B+x+%3D+%5Cfrac%7B5%7D%7B3%7D+%5C%5C+%5C%5C+%3D+%26gt%3B+zeros+%3D+%5Cfrac%7B5%7D%7B3%7D+%5C%3A+and+%5C%3A+%5Cfrac%7B5%7D%7B3%7D+%5C%5C+%5C%5C+now+%5C%5C+%5C%5C+plug+%5C%3A+value+%5C%3A+%3D+%26gt%3B+k+%3D+-+%5Cfrac%7B4%7D%7B7%7D+%5C%5C+%5C%5C+%3D+%26gt%3B+%282%28+-+%5Cfrac%7B4%7D%7B7%7D+%2B+1%29+%7Bx%7D%5E%7B2%7D+-+%287%28+-+%5Cfrac%7B4%7D%7B7%7D+%29+%2B+2%29x+%2B+%287%28+-+%5Cfrac%7B4%7D%7B3%7D+%29+-+3%29+%3D+0+%5C%5C+%5C%5C+%3D+%26gt%3B+%28+-+%5Cfrac%7B1%7D%7B7%7D+%29+%7Bx%7D%5E%7B2%7D+%2B+2x+-+7+%3D+0+%5C%5C+%5C%5C+%3D+%26gt%3B+%5Cfrac%7B1%7D%7B7%7D+%7Bx%7D%5E%7B2%7D+-+2x+%2B+7+%3D+0+%5C%5C+%5C%5C+%3D+%26gt%3B+%7B%28+%5Cfrac%7B1%7D%7B+%5Csqrt%7B7%7D+%7D%29+%7D%5E%7B2%7D+-+2%28+%5Cfrac%7B1%7D%7B+%5Csqrt%7B7%7D+%7D+x%29+%5Csqrt%7B7%7D+%2B+%7B+%5Csqrt%7B7%7D+%7D%5E%7B2%7D+%3D+0+%5C%5C+%5C%5C+%3D+%26gt%3B+%7B%28+%5Cfrac%7B1%7D%7B+%5Csqrt%7B7%7D+%7Dx+-+%5Csqrt%7B7%7D+%29%7D%5E%7B2%7D+%3D+0+%5C%5C+%5C%5C+%3D+%26gt%3B+%5Cfrac%7B1%7D%7B+%5Csqrt%7B7%7D+%7D+x+%3D+%5Csqrt%7B7+%7D+%5C%5C+%5C%5C+%3D+%26gt%3B+x+%3D+7+%5C%5C+%5C%5C+%3D+%26gt%3B+zeros+%5C%3A+%3D+7+%5C%3A+and+%5C%3A+7)
if "k=4" then roots are "5/3 and 5/3"
if "k=-4/7" then roots are 7 and 7
======================
HOPE IT WILL HELP YOU ☺☺☺
======================
DEVIL_KING ▄︻̷̿┻̿═━一
HERE IS YOUR ANSWER ☞
========================
if "k=4" then roots are "5/3 and 5/3"
if "k=-4/7" then roots are 7 and 7
======================
HOPE IT WILL HELP YOU ☺☺☺
======================
DEVIL_KING ▄︻̷̿┻̿═━一
Similar questions